Retrieval of CO Relative Column Abundance in the Martian Thermosphere From FUV Disk Observations by EMM EMUS. Issue 18 (21st September 2022) - Evans, J. S.; Correira, J.; Deighan, J.; Jain, S.; Al Matroushi, H.; Al Mazmi, H.; Chaffin, M.; Curry, S.; England, S.; Eparvier, F.; Fillingim, M.; Forget, F.; et al.
Abstract: Carbon monoxide (CO) is a sensitive tracer of the thermal profile and winds in Mars' middle atmosphere and the chemistry that balances CO2 in the whole atmosphere of Mars. The Emirates Ultraviolet Spectrometer (EMUS) onboard the Emirates Mars Mission Hope probe images Mars at ultraviolet wavelengths from approximately 100 to 170 nm. ΣCO/CO2, the column density ratio of CO to carbon dioxide, provides a sensitive measure of CO relative variability within the Martian thermosphere. Derived from the heritage of ΣO/N2 used at Earth, the ΣCO/CO2 algorithm uses emission from the CO Fourth Positive Group band system to derive the relative column abundance of CO above ∼70 km. We describe the EMUS ΣCO/CO2 algorithm, review the Level 3 data product, and discuss preliminary validation of the algorithm. The ΣCO/CO2 algorithm produces column density ratios that characterize the spatial structure and relative variability of CO abundance in the Martian thermosphere. Plain Language Summary: The Emirates Mars Ultraviolet Spectrometer onboard the Emirates Mars Mission observes light in a wavelength region referred to as far ultraviolet. This study focuses on far ultraviolet light that is produced by carbon monoxide (CO). Observations of far ultraviolet light can be used to determine the relative abundance of CO in the upper atmosphere of Mars. Variations in the relative abundance of CO over time and across different locations can provide valuable information regarding the temperatures and winds in the middle atmosphere of Mars, as well as the chemistry that balances the whole atmosphere of Mars. This study presents a method for converting observations of far ultraviolet light into relative abundances of CO in the upper atmosphere of Mars. Key Points: Emirates Ultraviolet Spectrometer (EMUS) observations provide large scale, high cadence, synoptic views of carbon monoxide (CO) relative column abundance in the lower thermosphere of Mars Significant variability in CO brightness and relative column abundance is regularly observed in EMUS disk images Observed variability of CO relative column abundance in local time, latitude, and solar longitude is inconsistent with model predictions